Материалы к систематике, экологии и паразитофауне пресмыкающихся Курильских островов. Сообщение I - Щербак, Н.Н.; Шарпило, В.П. (Вестник зоологии, 1969)
37 individuals of 4 species of Reptilia were obtained by the authors during the first Kuril expedition of the Institute of Zoology of the Academy of Sciences of the Ukrainian SSR (1965).
In the communication I the data are presented on phollidosis, the life-time coloration, nutrition, attitude to the temperature of Far-Eastern Eumeces latiscutatus and its parasites — Kulironema markovi gen n. sp. n. (Nematodes), Centrorhynchus sp. (Acan-thocephala).